2013
DOI: 10.1016/j.mmcr.2013.01.004
|View full text |Cite
|
Sign up to set email alerts
|

A disseminated infection with the antifungal-multiresistant teleomorphic fungus Neocosmospora vasinfecta in a patient with acute B-lymphoblastic leukemia

Abstract: We report on a fatal invasive infection due to the ascomycetous fungus Neocosmospora vasinfecta, in a 20-year-old European patient suffering from an acute lymphoblastic leukemia. The infection could not be controlled by a bitherapy combining liposomal amphotericin B and voriconazole. This is the second case of disseminated infection reported with this unusual fungus, which develops under its teleomorphic state, is fully resistant to all systemic antifungals, and which is known to live in tropical countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…These features include: (1) production of round, single-celled ascospores, instead of ellipsoidal, multiseptate ascospores of many Fusarium spp. (Smith, 2007); (2) the majority of spores are released through cirrhi that are most likely splash-dispersed; and (3) perithecia are larger than those produced by F. graminearum (300 μm in F. neocosmosporiellum compared with 180 μm in F. graminearum ) (Calaça et al, 2013; Gabriel et al, 2013; Sun et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These features include: (1) production of round, single-celled ascospores, instead of ellipsoidal, multiseptate ascospores of many Fusarium spp. (Smith, 2007); (2) the majority of spores are released through cirrhi that are most likely splash-dispersed; and (3) perithecia are larger than those produced by F. graminearum (300 μm in F. neocosmosporiellum compared with 180 μm in F. graminearum ) (Calaça et al, 2013; Gabriel et al, 2013; Sun et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In prior research, we studied the homothallic, cereal pathogen F. graminearum (FSAMSC) with particular emphasis on development and function of perithecia, as well as production of mycotoxins and other secondary metabolites (Gaffoor et al, 2005; Sikhakolli et al, 2012; Wang et al, 2012, 2018; Trail et al, 2017; Kim et al, 2018). Recently, we began a study of perithecium development in homothallic F. neocosmosporiellum (formerly Neocosmospora vasinfecta ; Geiser et al, 2013), a member of the FSSC that is reported to be pathogenic on peanut and soybean (Dau et al, 2010; Pan et al, 2010; Sun et al, 2014; Greer et al, 2015), and an opportunistic pathogen of humans (Cornely et al, 2001; Gabriel et al, 2013). This cosmopolitan species has also been reported on infected soybean cyst nematodes (Gintis et al, 1983) and dung of diverse herbivores (Calaça et al, 2013).…”
Section: Introductionmentioning
confidence: 99%